Du tourisme de masse au tourisme durable ? - Claire Weishar (Confins)
Tourism is one of the major challenges of the 21st century. Ever more informed about the consequences of mass tourism and sensitized to Sustainable Development, consumer-tourists are gradually formulating the demand for more sustainable tourism.